2022
DOI: 10.1007/s41347-022-00261-7
|View full text |Cite
|
Sign up to set email alerts
|

Online Mindfulness-Based Cognitive Therapy for People with Parkinson’s Disease and Their Caregivers: a Pilot Study

Abstract: Anxiety and depression are common non-motor symptoms of Parkinson’s disease (PD). Caregivers of people with PD may experience severe caregiver burden. This study explored the feasibility and potential benefits of an online mindfulness-based cognitive therapy (MBCT) intervention for improving anxiety and depressive symptoms in people with PD and their caregivers (ClinicalTrials.gov NCT04469049, 7/8/2020). People with PD or parkinsonism and anxiety and/or depressive symptoms and caregivers of people with PD part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…A number of single-arm trials investigating the effect of mindfulness and meditation therapies in patients with PD have also been conducted [38][39][40][41][42][43]. In general, beneficial effects of a certain degree on mental health, emotion function, cognitive function, and motor function were discovered in patients with PD after mindfulness or meditation therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of single-arm trials investigating the effect of mindfulness and meditation therapies in patients with PD have also been conducted [38][39][40][41][42][43]. In general, beneficial effects of a certain degree on mental health, emotion function, cognitive function, and motor function were discovered in patients with PD after mindfulness or meditation therapies.…”
Section: Discussionmentioning
confidence: 99%
“…As such, alleviating PD CP depression has the potential to simultaneously improve dyadic well-being and PwPD disease burden. Previous studies have demonstrated that dyadic mindfulness interventions [89][90][91] and multidisciplinary rehabilitation programs [92] improve depression in PwPD and their CP. To our knowledge, this study is the first cycling intervention to improve depressive symptoms experienced by PD CP.…”
Section: Effects Of Vr Tandem Cycling On Cpmentioning
confidence: 99%
“…As such, the lack of improvement in both may explain our findings. Further, the current literature has only described cognitive behavioral therapy [91,96,97] and patient education programs [98] for alleviating PD CP anxiety; exercise interventions have yet to be examined for improving these dimensions of well-being, making our study's preliminary findings a starting point for further analysis.…”
Section: Effects Of Vr Tandem Cycling On Cpmentioning
confidence: 99%
“…By title and keyword identification, the research topics are summarized in Table 1. There were 31% of the research topics related to telemedicine (n = 5) (20, 24, 26, 28, 34) and cognitivebehavioral therapy (n = 6) (22,24,29,30,35,40). Cognitive behavioral therapy has gradually become a family-centered research focus of Parkinson's since 2010, while telemedicine has gradually become a research hotspot since 2017 because of its technical reasons.…”
Section: Distribution Of Research Topicsmentioning
confidence: 99%